PENGARUH METODE ROLE PLAYING BERBANTUAN KOMIK TERHADAP HASIL BELAJAR PKN KELAS III SD - Prasodjo, Bayu; Sabri, Tahmid; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research purpose is to know the influence of applying role playing methode assisted by comics in learning Citizenship Education to the learning result of third grade students of Bawamai Primary School Pontianak. The research method is experimental as Pre-Experimental Design of non equivalent control group design. The population of all students from two classes is 64 people, the sample of this research is IIIB students with 33 people as experimental classes and IIIC as a control class with 31 people. The Used Data collection techniques are measurement techniques and data collector tools are written tests of multiple choice. The average post-test results of experimental class is 79.06 and the control post-test average is 71.89. The result of hypothesis test using t-test (T-test) obtained t count = 36,10 whereas for dk (33 + 31-2 = 62) with significance level ? = 5% obtained t table = 1,676, which means t count> t tabel, , this proves that there is an effect of applying role playing role-playing asisted by comics in learning civic education. Based on result of calculation of effect size (ES) obtained ES = 0.67 which included medium criteria, about 0,67 <0,8. Thus it can be said that the application of role playing role playing comic in study of Citizenship Education gives positive influence to student learning result of third class Bawamai Primary School Pontianak. Keywords: Influence, Role Playing Method, Comics, Citizenship Education, Learning                  Result.